Pengaruh Influencer Najwa Shihab dan FOMOI di Instagram Terhadap Opini Publik(Studi Kasus pada Postingan Peringatan Darurat Garuda Biru - Fadhil Dzaky Beta Rizqullah; Fikri Shofin Mubarok (INDO PUBLISHING, 2025)
Social media has become a primary platform for shaping public opinion, especially on urgent and sensitive issues. One such example is the peringatan darurat Garuda Biru phenomenon posted by the Instagram account @najwashihab, which received significant public response. This study aims to determine the influence of influencers and Fear of Missing Out (FoMO) behavior on public opinion regarding the emergency alert post. The study uses the Uses and Gratifications theory, which emphasizes the active role of audiences in selecting and using media to fulfill their informational needs. This research employs a quantitative method. Data were collected through questionnaires distributed to 100 respondents who follow the Instagram account @najwashihab, with the sample size calculated using the Slovin formula and selected through purposive sampling. The results show that the t-test for the influencer variable affecting public opinion produced a t-value of 4,437 with a significance value of less than 0,001. Using a significance threshold of 0,05, the t-table value was 0,1660. Therefore, it can be concluded that H0 is rejected and H1 is accepted, meaning that the influencer variable (X1) has a significant influence on public opinion (Y). Furthermore, the FoMO variable affecting public opinion had a t-value of 3,725 with a significance value also less than 0,001. With the same threshold, the t-table value was 0,1660, leading to the conclusion that H0 is accepted and H2 is rejected, indicating that the FoMO variable (X2) does not have a significant influence on public opinion (Y). This study is limited to only 100 respondents who are followers of the @najwashihab Instagram account a relatively small number compared to the account’s total followers of over 24 million. .